The Influence of Seed Sowing Times and Rate of Fertilizer Application on Leaf Surface Formation - Sa’dullayevich, Kushmatov Bakhtiyor; Bakhtiyorovich, Mavlanov Laziz (American Journal of Biodiversity, 2025)
This study examines the influence of sowing dates, seed rates, and mineral fertilizer application rates on the leaf surface formation of the triticale variety Sardor. Through scientific analysis, the research identifies optimal agricultural practices that enhance leaf development, which is crucial for improving photosynthetic efficiency and overall crop yield. Experimental data demonstrate how variations in these factors affect leaf surface area, contributing to better understanding and management of triticale cultivation. The findings provide practical recommendations for optimizing sowing and fertilization strategies to maximize the growth potential and productivity of Sardor triticale.